ROS-mediated enhanced transcription of CYP38 promotes the plant tolerance to high light stress by suppressing GTPase activation of PsbO2 - Wang, Yongqiang; Zeng, Lizhang; Xing, Da (Frontiers in Plant Science, 2015)
As a member of the Immunophilin family, cyclophilin38 (CYP38) is discovered to be localized in the thylakoid lumen, and is reported to be a participant in the function regulation of thylakoid membrane protein. However, the molecule mechanisms remain unclear. We found that, CYP38 plays an important role in the process of regulating and protecting the plant to resist high light (HL) stress. Under HL condition, the gene expression of CYP38 is enhanced, and if CYP38 gene is deficient, photochemistry efficiency and chlorophyll content falls distinctly, and excessive reactive oxygen species (ROS) synthesis occurs in the chloroplast. Western blot results showed that the D1 degradation rate of cyp38 mutant plants is faster than that of wide type (WT) plants. Interestingly, both gene expression and activity of PsbO2 were drastically enhanced in cyp38 mutant plants and less changed when the deleted gene of CYP38 was restored under HL treatment. This indicates that CYP38 may impose a negative regulation effect on PsbO2, which exerts a positive regulation effect in facilitating the dephosphorylation and subsequent degradation of D1. It is also found that, under HL condition, the cytoplasmic calcium ([Ca2+]cyt) concentration and the gene expression level of calmodulin 3 (CaM3) arose markedly, which occurs upstream of CYP38 gene expression. In conclusion, our results indicate that CYP38 plays an important role in plant strengthening HL resistibility, which provides a new insight in the research of mechanisms of CYP38 protein in plants.